2011
DOI: 10.3892/etm.2011.433
|View full text |Cite
|
Sign up to set email alerts
|

Association between the M235T polymorphism of the AGT gene and cytokines in patients with hypertension

Abstract: Abstract. The aim of the present study was to explore the association between the M235T polymorphism of the angiotensinogen (AGT) gene and cytokines in patients with essential hypertension (EH). A total of 300 patients with EH and an agematched control group of 150 individuals without EH, secondary hypertension, myocardial infarction and diabetes were enrolled in this study. Polymerase chain reaction combined with restriction fragment length polymorphism (PCR-RFLP) was used to detect variation in the target ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
4
8
0
2
Order By: Relevance
“…Instead, Liu and associates 46 observed the rs5186-hypertension association in Asians and Caucasians in support of findings reported elsewhere. 45,47 Our meta-analysis also suggests an association of rs699 with hypertension, similar to studies conducted in Asians, 48,49 while no association between any of the common SNPs found in RAAS genes and hypertension has been reported by other authors. 50 The inconsistent findings may be attributable to differences in study design, specifically generalization of hypertension by some studies as hypertension, [45][46][47] while Sun and colleagues 50 investigated the salt-sensitive hypertension phenotype.…”
Section: Discussionsupporting
confidence: 89%
“…Instead, Liu and associates 46 observed the rs5186-hypertension association in Asians and Caucasians in support of findings reported elsewhere. 45,47 Our meta-analysis also suggests an association of rs699 with hypertension, similar to studies conducted in Asians, 48,49 while no association between any of the common SNPs found in RAAS genes and hypertension has been reported by other authors. 50 The inconsistent findings may be attributable to differences in study design, specifically generalization of hypertension by some studies as hypertension, [45][46][47] while Sun and colleagues 50 investigated the salt-sensitive hypertension phenotype.…”
Section: Discussionsupporting
confidence: 89%
“…TNF alpha can not only damage blood vessels directly, but also cause its function disorder through increasing the gener- ate of blood vessel contraction factors and reducing the release of vasodilatation factors [22]. This study showed that, compared with control group, the serum TNF alpha level of Hui and Han hypertension group was higher, and the differences were statistically significant (P < 0.01), and which was in accordance with the past research results [23,24]. Previous study found that TNF-α was an important cytokine, which mediated inflammatory response and immune regulation, and played important role in the occurrence and regulation of vascular endothelial cells [25].…”
Section: Discussionsupporting
confidence: 90%
“…The main objective of this study was to get the confirmation of the association of AGT M235T polymorphism and essential hypertension in Myanmar population. Our results showed the TT genotypes is more common in hypertensive than those of normotensives The present study was similar to association between AGT M235T polymorphism and essential hypertension in China population [14]. The AGT M235T was associated with hypertension and independent risk factors of hypertension in the Japanese (OR=1.59 (1.25-2.01) p=0.0001) [15].…”
Section: Discussionsupporting
confidence: 86%